TCT RUSSIA — XIV MOSCOW INTERNATIONAL COURSE ON ROENTGEN-ENDOVASCULAR DIAGNOSTICS AND THERAPY BECAME A REVIEW OF INNOVATIVE TECHNOLOGIES AND METHODS IN CARDIOVASCULAR SURGERY (Рациональная фармакотерапия в кардиологии)
.